Myeloid-associated lipin-1 transcriptional co-regulatory activity is atheroprotective. (August 2021) - Blackburn, Cassidy M.R.; Schilke, Robert M.; Vozenilek, Aimee E.; Chandran, Sunitha; Bamgbose, Temitayo T.; Finck, Brian N.; Woolard, Matthew D.
Abstract: Background and aims: Atherosclerosis is the most prominent underlying cause of cardiovascular disease (CVD). It is initiated by cholesterol deposition in the arterial intima, which causes macrophage recruitment and proinflammatory responses that promote plaque growth, necrotic core formation, and plaque rupture. Lipin-1 is a phosphatidic acid phosphohydrolase for glycerolipid synthesis. We have shown that lipin-1 phosphatase activity promotes macrophage pro-inflammatory responses when stimulated with modified low-density lipoprotein (modLDL) and accelerates atherosclerosis. Lipin-1 also independently acts as a transcriptional co-regulator where it enhances the expression of genes involved in β-oxidation. In hepatocytes and adipocytes, lipin-1 augments the activity of transcription factors such as peroxisome proliferator-activated receptor (PPARs). PPARs control the expression of anti-inflammatory genes in macrophages and slow or reduce atherosclerotic progression. Therefore, we hypothesize myeloid-derived lipin-1 transcriptional co-regulatory activity reduces atherosclerosis. Methods: We used myeloid-derived lipin-1 knockout ( lipin-1mKO ) and littermate control mice and AAV8-PCSK9 along with high-fat diet to elicit atherosclerosis. Results: Lipin-1mKO mice had larger aortic root plaques than littermate control mice after 8 and 12 weeks of a high-fat diet. Lipin-1mKO mice also had increased serum proinflammatory cytokine concentrations, reduced apoptosis in plaques, and larger necrotic cores in the plaques compared to control mice. Conclusions: Combined, the data suggest lipin-1 transcriptional co-regulatory activity in myeloid cells is atheroprotective. Graphical abstract: Image 1 Highlights: Myeloid-derived lipin-1 transcriptional co-regulatory activity is atheroprotective. Lipin-1m KO mice have increased plaque area and IL-23 gene expression. Lipin-1m KO mice have larger plaque necrotic cores.